Factors Influencing Discontinuation of Long-Term Contraceptive Methods - Dayu Marista; Mochammad Bagus Qomaruddin; Oedojo Soedirham (Science Midwifery, 2022)
Discontinuation of contraception represents a very important reproductive health problem and has adverse consequences on women's reproductive health outcomes. Worldwide, a large number of women become at risk of conception after discontinuation of contraception. The purpose of this study was to determine the reasons for discontinuation and the factors that influence the discontinuation of long-term contraceptive methods. The research method used is a literature review with article searches using four databases consisting of Pubmed, Sage, Science Direct and Proquest with a publication range of 2012-2022. The keywords used are associated factor and discontinuation of long acting reversible contraception. The findings indicate that the factors that influence the long-term discontinuation of contraceptive methods are marital status, education, counseling, age, parity, occupation, contraceptive satisfaction, partner support, duration to health facilities, desire to get pregnant again and side effects. The most common reason for discontinuing a long-term contraceptive method is due to health problems or side effects. Therefore, health workers should properly advise women about the common side effects of using long-term contraceptive methods and how to manage these side effects.